Models of concurrent program running in resource constrained environment - Rahozin, D. (Проблеми програмування, 2020)
The paper considers concurrent program modeling using resource constrained automatons. Several software samples are considered: real time operational systems, video processing including object recognition, neural network inference, common linear systems solving methods for physical processes modeling. The source code annotating and automatic extraction of program resource constraints with the help of profiling software are considered, this enables the modeling for concurrent software behavior with minimal user assistance. В работе рассмотрено моделирование параллельных программ с помощью автоматов с ресурсными ограничениями. Рассмотрен ряд примеров программ: операционные системы реального времени, обработка видео и распознавание образоив в видеопотоке, вывод в нейросетях, типовые методы решения систем линейных уравнений для моделирования физических процессов. Рассмотрено аннотирование исходного кода и автоматическое получение ресурсных ограничений программы с помощью программ-профилировщиков, что позволяет моделировать поведение параллельно программы с минимальной помощью пользователя. У роботі розглянуто моделювання паралельних програм за допомогою автоматів з ресурсними обмеженнями. Розглянуто певні приклади програм: операційні системи реального часу, обробка відео та розпізнавання образів у відеопотоці, вивід у нейромережах, типові методи розв’язку систем лінійних рівнянь для моделювання фізичних процесів. Розглянуто анотування вихідного коду та автоматичне отримання ресурсних обмежень програми за допомогою програм-профайлерів, що дозволяє моделювати поведінку паралельної програми з мінімальною допомогою користувача.